Coordination of the head of district in administering government in Parigi, Parigi Moutong Regency, Central Sulawesi Province - Hidayah, Andi Muh. Riskil; Wardana, Andy (Tamalanrea: Journal of Government and Development (JGD), 2024)
This study aims to determine the coordination of head of district (Camat) in administering government in Parigi District, Parigi Mourong Regency, Central Sulawesi Province. The study used a qualitative approach with descriptive methods. Taking informants by determining five people as informants. In order to obtain the data, we used Dann Sugandha’s theory about internal coordination and external coordination, and also used observation, interviews, and documentation in data collection methods. To maintain the objectivity of the study, we used the data analysis technique of Miles and Huberman’s interactive model. The study reveals that internal coordination between the head of district and his subordinate staff in the form of providing reports, providing suggestions and proposals, providing instructions has been carried out well. External coordination was coordination carried out between the District Government and the government in the Parigi District area. External coordination between the district governments has not been implemented optimally because there remains weaknesses or lack of coordination in the administration of government between the district government and the government in the Parigi district area which has not been implemented well, so development has not been optimal.